EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10893092 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1020 ZenodoArchiveConcept: 10893091
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found